On‐treatment HCV RNA as a predictor of sustained virological response in HCV genotype 3–infected patients treated with daclatasvir and sofosbuvir. (16th June 2016) - Kowdley, Kris V.; Nelson, David R.; Lalezari, Jacob P.; Box, Terry; Gitlin, Norman; Poleynard, Gary; Rabinovitz, Mordechai; Ravendhran, Natarajan; Sheikh, Aasim M.; Siddique, Asma; Bhore, Rafia; Noviello, Stephanie; et al.
Abstract: Background and Aims: Many currently available direct‐acting antiviral (DAA) regimens are less effective against HCV genotype 3 than against other HCV genotypes. The all‐oral, pangenotypic DAA combination of daclatasvir (NS5A inhibitor) + sofosbuvir (nucleotide NS5B inhibitor) was studied in genotype 3–infected treatment‐naive and ‐experienced patients (ALLY‐3) who achieved rates of sustained virological response at post‐treatment Week 12 (SVR12) of 90 and 86% respectively. In this analysis, we assessed whether on‐treatment responses to daclatasvir + sofosbuvir in genotype 3–infected patients could predict treatment outcome. Methods: In ALLY‐3, treatment‐naive and ‐experienced patients, with or without cirrhosis, were treated with daclatasvir + sofosbuvir for 12 weeks. HCV RNA kinetics and categorical virological responses on treatment were assessed. The proportions of responders and nonresponders by study week, and time to first undetectable HCV RNA, were analysed for utility in predicting treatment outcome. Results: Overall, HCV RNA levels declined rapidly during Week 1 of treatment in both treatment‐naive and ‐experienced cohorts. Although patients with cirrhosis had a slower initial virological response as measured by the proportion of patients with HCV RNA below the lower limit of quantification at Week 1, responses converged thereafter. Positive and negative predictive values calculated for on‐treatment responses were generally comparable with the overall SVR12 rate and were therefore limited indicators of outcome. SVR12 rates were not impacted by time to first undetectable HCV RNA. Conclusions: On‐treatment responses are not useful predictors of ultimate virological response to the daclatasvir + sofosbuvir regimen.